Dynamic monitoring of tropospheric ozone concentrations in northeast and Midwest Brazil: insights into seasonal variations and climatic influences - Souza, Amaury de; de Medeiros, Elias Silva; Özonur, Deniz; de Oliveira-Júnior, José Francisco; Abreu, Marcel Carvalho; Pobocikova, Ivana; Nune, Raquel Soares Casaes (International Journal of Engineering and Technology, 2024)
Rapid economic transformations, the urbanization process, and the intensification of industrialization have resulted in a notable increase in ozone (O3) emissions, particularly in the Northeast and Central-West regions of Brazil. To monitor the tropospheric ozone column (TCO) over these regions, the Aura Ozone Monitoring Instrument (OMI) was utilized for long-term, large-scale dynamic monitoring from 2008 to 2016. Seasonal variations in O3 concentration revealed that spring exhibited higher concentrations compared to winter. However, winter showed higher O3 concentrations than summer and autumn. Monthly variations displayed cyclical variability, with low values observed in April-June for Campo Grande and in October for Maceió, while high values were observed in October for Campo Grande and in May for Maceió. The spatio-temporal distribution of O3 concentration was influenced by natural and anthropogenic factors. TCO concentration showed positive correlations with temperature and wind. The monthly TCO demonstrated seasonal variation in both cities. Linear regression analysis indicated an increasing trend in TCO due to latitudinal variation between Maceió and Campo Grande during the study period.